Ground-based optical observation system for LEO objects. Issue 3 (1st August 2015) - Yanagisawa, T.; Kurosaki, H.; Oda, H.; Tagawa, M.
Abstract We propose a ground-based optical observation system for monitoring LEO objects, which uses numerous optical sensors to cover a vast region of the sky. Its potential in terms of detection and orbital determination were examined. About 30 cm LEO objects at 1000 km altitude are detectable using an 18 cm telescope, a CCD camera and the analysis software developed. Simulations and a test observation showed that two longitudinally separate observation sites with arrays of optical sensors can identify the same objects from numerous data sets and determine their orbits precisely. The proposed system may complement or replace the current radar observation system for monitoring LEO objects, like space-situation awareness, in the near future.